The Influence Of Cultural Elements On The Purchasing Decisions Of Hair Care Products In India - Meenakshi, P. Pon; M. Nandhini, M. Nandhini; S. Revathy, S. Revathy; K. Mahalakshmi, K. Mahalakshmi; M. Nithyasri, M. Nithyasri (Journal of Neonatal Surgery, 2025)
The cultural landscape of India plays a pivotal role in shaping consumer behavior towards beauty care products, encompassing categories such as skincare, haircare, eye care, and facial treatments. India’s deep-rooted cultural heritage, enriched by centuries of tradition and societal norms, has a profound influence on beauty standards and preferences. There is a notable inclination towards products with natural ingredients, fairness-enhancing solutions, and Ayurvedic formulations, reflecting a cultural preference for holistic beauty. Simultaneously, the growing influence of Western beauty trends is steering consumers toward more modern, clinical beauty products. This study examines the confluence of traditional values and contemporary aspirations in shaping the purchasing decisions of Indian consumers, highlighting the evolving expectations from beauty brands and their need to adapt to these dynamic cultural influences.